Review on Laboratory tests for Diagnosis of Hepatitis C Virus Infection - Abbas Morovvati; somayeh dehghani sanij; Ashkan Dirbaziyan; homa Azadegan; shima Aghaei; hasan vahidi emami (بیولوژی کاربردی, 2019)
Abstract Hepatitis C virus (HCV) infection is associated with chronic hepatitis, cirrhosis, and hepatocellular carcinoma. This review summarizes the pathogenesis and significance of serological and molecular-based assays and new methods in the diagnosis and management of HCV infection after reading this article, readers should be able to describe laboratory tests used in the diagnosis and management of HCV infection. They should also be able to describe the general principles for selecting the most appropriate laboratory test for diagnosis, therapeutic decision making, and assessment of virologic response to therapy. New methods for diagnosis of HCV virus infection could help for HCV detection and virus Genotypes in patient. Molecular methods are very sensitive and specific for RNA diagnosis and uses of this test for HCV genotypes Because HCV genotypes different response to druges.HCV genotypes detection could help for follow up treatment by interferon of patient. Keywords: hepatitis C virus, hepatitis, hepatocellular carcinoma, molecular diagnostics